Aktivitas Anti Hiperurisemia Ekstrak Akar Kaik-kaik (Uncaria cordata. L. Merr) pada Mencit (Mus muscullus) yang Diinduksi Kalium Oksonat - Nurhamidah Nurhamidah; Rima Fadillah; Elvinawati Elvinawati; Dewi Handayani (Universitas Andalas, 2022)
Consuming food containing high level of purin leads to increase uric acid in the blood which, in turn, cause hyperuricemia or high uric acid level. The use of improper allopurinol for hyperuricemia medication that doesn’t follow medical doctor’s prescription can give harmful side effect. It is therefore required to use an alternative safe medication. Uncaria cordata (Lour.) Merr.) is a plant often used for medication of high levels of blood uric acid by communities in Pasar Ngalam village, Bengkulu Province. This research aims to evaluate the potency of extracted compounds from Uncaria cordata (Lour.) Merr.) in reducing uric acid of Mus musculus suffering from hyperuricemia. This research is a laboratory experiment using completed random design. As many as 25 Mus musculus were divided into 5 groups of treatment: PN = normal treatment, PA = treated with allopurinol, P1 – P3 = treated with extracted compound of Uncaria cordata (Lour.) Merr.) with a dose of 5.3 mg/30gBW (P1); 10.6 mg/30gBW (P2); and 21.2 mg/30gBW (P3). In order for Mus musculus to suffer from high uric acid level, potassium oxonate-induced hyperuricemia was injected. The result showed that extracted compounds of Uncaria cordata (Lour.) Merr.) using ethanol exhibited antihyperuricemia proven by decline of uric acid level of Mus musculus from hyperuricemia on each given dose. Decreasing uric acid level for each given dose of ethanol extract (5.3 mg/30gBW, 10.6mg/30gBW and 21.2mg/30gBW) was not significant different (0.541; with a ³0.05).